Enhancement of gas permeation properties of polybenzimidazoles by systematic structure architecture - Kumbharkar, Santosh C.; Karadkar, Prasad B.; Kharul, Ulhas K. (Journal of Membrane Science, 2006)
Systematic structural variations in thermally stable polybenzimidazole (PBI) are explored that led to a substantial improvement in gas permeation properties. Physical property determinations revealed that incorporation of hexafluoroisopropylidene and tert-butyl groups led to amorphous polymers with slightly lowered thermal stability and decreased chain packing. PBI based on 4,4'-(hexafluoroisopropylidene)bis(benzoic acid) and 5-tert-butyl isophthalic acid exhibited 10-40 times higher permeability, while changes in selectivities for industrially important pairs ranged from modest decrease of 75% or less than that of PBI based on isophthalic acid. The O-2/N-2 selectivity was almost doubled in case of PBI based on 5-tert-butyl isophthalic acid. Gas diffusion coefficients were estimated from solubility and permeability coefficient determinations. These, along with dual-mode sorption parameters estimated from sorption isotherms provided an insight towards variations in permeation behavior. The permeability predictions for heavier gases in isophthalic acid based PBI correlated well with physical properties. The occurrence of permeation characteristics (especially P-H2 and P-H2/P-N2) near Robeson's upper bound, high thermal stability and good solvent solubility achieved by these structural modifications depicted the potential of this family of polymers as gas separation membrane materials. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Diffusion; Gas permeation; Polybenzimidazole; Sorption; thermal stability

Gas permeation in amine functionalized silicon rubber membranes - Achalpurkar, Manoj P.; Kharul, Ulhas K.; Lohokare, Harshada R.; Karadkar, Prasad B. (Separation and Purification Technology, 2007)
Silicon rubber (SR) based thin film composite (TFC) membranes find increasing applicability in various industrial separations owing to its excellent thermal and chemical stability. The functionalization of SR would provide enhanced separation characteristics for certain separation applications. The present research focuses on gas permeation properties of dense and thin film composite membranes based on amine substituted silicon rubber (ASR) and unsubstituted silicon rubber (SR). The dense membrane sorption analysis indicated that presence of amine functionality in ASR increased pressure dependant CO2 sorption capacity. Owing to this, an elevation Of CO2 permeability by 15% and CO2 based selectivities by 22-34% in comparison to that of unsubstituted SR was observed. The TFC membranes with SR and ASR as the selective layer on the top of different ultrafiltration (UF) supports with varying properties based on polyacrylonitrile and polysulfone were prepared. The effects of crucial parameters that affected TFC membrane performance, viz., coating solution concentration, UF support membrane porosity and nature of materials were investigated. The preparation of ASR based TFC membranes was demonstrated with a simple crosslinking agent-glutaraldehyde while analyzing effects of crosslinking time on their permeation properties. Polyacrylonitrile (PAN) was found to be better support layer material for ASR based TFC formation than polysulfone (PSF). Thin defect free coating layer can be obtained by appropriate combination of coating solution concentration and support UF membrane porosity. The analysis of effective skin layer thickness of TFC membranes indicated that careful optimization of these parameters is necessary to achieve defect free TFC membranes possessing a good combination of permeance and selectivity. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: Carbon dioxide; Gas permeation; silicon rubber; thin film composite membrane

Gas sorption and transport in polyarylates: effect of substituent symmetry and polarity - Karadkar, Prasad B.; Kharul, Ulhas K.; Bhole, Yogesh S.; Badhe, Yogesh P.; Tambe, Sanjeev S.; Kulkarni, Bhaskar D. (Journal of Membrane Science, 2007)
The gas sorption properties of polyarylates based on bisphenol-A possessing symmetric/asymmetric substitution by nonpolar -CH3 group and symmetrically linked terephthalic acid were examined. The effects of substitution of polar bromine on terephalic acid moiety of polyarylate based on asymmetrically substituted bisphenol were also studied for physical, sorption and transport properties. The estimation of dual mode sorption parameters, solubility and diffusion coefficient revealed that nature of the substituent and substitution type plays a crucial role in depicting permeation properties. An asymmetric substitution by -CH3 group increased solubility coefficient of pure gases (N-2, O-2, CH4 and CO2) up to 27% and symmetric substitution increased the same up to 106%. This was coupled with 7-35% increase in solubility selectivity in both cases of substitution, which ascertained the usefulness of methyl group substitution in polyarylates based on terephalic acid. The pressure dependency of solubility coefficients and solubility selectivity was also investigated for these polyarylates. The sorption and transport properties of these polyarylates correlated well with physical properties of polyarylates and gases studied. The sorption/desorption kinetics of symmetrically substituted TMBisA-T was performed in order to deduce time dependent sorption behavior and to evaluate diffusivity coefficient. The apparent diffusion coefficients from sorption kinetics, desorption kinetics and from steady-states permeation-sorption were compared. The diffusion coefficients of CH4 and N-2 deduced by these methods correlated well with each other. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: Diffusion; kinetics; permeation; polyarylates; Sorption

Nitration and amination of polyphenylene oxide: synthesis, gas sorption and permeation analysis - Bhole, Yogesh S.; Karadkar, Prasad B.; Kharul, Ulhas K. (European Polymer Journal, 2007)
A high degree of nitration of polyphenylene oxide (PPO) was successfully achieved by carefully optimizing synthetic protocol. The reduction of nitro group to amino could be done quantitatively. The physical properties of formed polymers were investigated and correlated with gas sorption and permeation properties. The formed polymers were amorphous in nature as revealed by wide angle X-ray diffraction spectra. An increase in the packing density in comparison to unsubstituted PPO as a result of induced polarity was indicated by lowering of fractional free volume and d-spacing. The substitution by either nitro or amino group increased the chain stiffness as revealed by the dynamic mechanical analysis. Though both, nitro and amino group substitution on PPO led to a decrease in pure gas permeability, the selectivity of various gas pairs was increased by these substitutions. The gas sorption analysis revealed that both, solubility selectivity and diffusivity selectivity were increased by these polar group substitutions. The nitro group substitution was more effective in improving solubility selectivity, while amino group substitution was more effective in improving diffusivity selectivity. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: Amination; nitration; permeation; polyphenylene oxide; Sorption